On the Adjustment Time in Neo-Classical Growth Models - Sato, K. (Review of Economic Studies, 1966)
Journal Article On the Adjustment Time in Neo-classical Growth Models Get access K. Sato K. Sato United Nations, New York Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 33, Issue 3, July 1966, Pages 263–268, https://doi.org/10.2307/2974420 Published: 01 July 1966